Healthcare-associated multispecies outbreaks of OXA-48–positive carbapenemase-producing Enterobacteriaceae in a Singapore tertiary-care hospital. (14th March 2022) - Venkatachalam, Indumathi; How, Molly Kue Bien; Ko, Karrie Kwan Ki; Abdul Rahman, Nurdyana Binte; Conceicao, Edwin Philip; Aung, May Kyawt; Aung, Myat Oo; Yang, Yong; Tan, Kwee Yuen; Sim, Jean Xiang Ying; Lee, Lai Chee; Ling, Moi Lin
Abstract: Objective: To describe OXA-48–like carbapenem-producing Enterobacteriaceae (CPE) outbreaks at Singapore General Hospital between 2018 and 2020 and to determine the risk associated with OXA-48 carriage in the 2020 outbreak. Design: Outbreak report and case–control study. Setting: Singapore General Hospital (SGH) is a tertiary-care academic medical center in Singapore with 1, 750 beds. Methods: Active surveillance for CPE is conducted for selected high-risk patient cohorts through molecular testing on rectal swabs or stool samples. Patients with CPE are isolated or placed in cohorts under contact precautions. During outbreak investigations, rectal swabs are repeated for culture. For the 2020 outbreak, a retrospective case–control study was conducted in which controls were inpatients who tested negative for OXA-48 and were selected at a 1:3 case-to-control ratio. Results: Hospital wide, the median number of patients with healthcare-associated OXA-48 was 2 per month. In the 3-year period between 2018 and 2020, 3 OXA-48 outbreaks were investigated and managed, involving 4 patients with Klebsiella pneumoniae in 2018, 55 patients with K. pneumoniae or Escherichia coli in 2019, and 49 patients with multispecies Enterobacterales in 2020. During the 2020 outbreak, independent risk factors for OXA-48 carriage on multivariate analysis (49 patients and 147 controls) were diarrhea within the preceding 2 weeks (OR, 3.3; 95% CI, 1.1–10.7; P = .039), contact with an OXA-48–carrying patient (OR, 8.7; 95% CI, 1.9–39.3; P = .005), and exposure to carbapenems (OR, 17.2; 95% CI, 2.2–136; P = .007) or penicillin (OR, 16.6; 95% CI, 3.8–71.0; P < .001). Conclusions: Multispecies OXA-48 outbreaks in our institution are likely related to a favorable ecological condition and selective pressure exerted by antimicrobial use. The integration of molecular surveillance epidemiology of the healthcare environment is important in understanding the risk of healthcare–associated infection to patients.